Relationship Between Particle Properties and Immunotoxicological Effects of Environmentally-Sourced Microplastics - Beijer, Nick R. M.; Dehaut, Alexandre; Carlier, Maxim P.; Wolter, Helen; Versteegen, Ron M.; Pennings, Jeroen L. A.; de la Fonteyne, Liset; Niemann, Helge; Janssen, Henk M.; Timmermans, Belinda G.; Mennes, Wim; Cassee, Flemming R.; et al. (Frontiers in Water, 2022)
Background: Concerns on microplastics (MPs) in food are increasing because of our increased awareness of daily exposure and our knowledge gap on their potential adverse health effects. When particles are ingested, macrophages play an important role in scavenging them, potentially leading to an unwanted immune response. To elucidate the adverse effects of MPs on human health, insights in the immunotoxicity of MPs are essential. Objectives: To assess the effect of environmentally collected ocean and land weathered MP particles on the immunological response of macrophages using a state-of-the art in vitro immunotoxicity assay specifically designed for measuring particle toxicity. Methods: Environmentally-weathered macroplastic samples were collected from the North Pacific Subtropical Gyre and from the French coastal environment. Macroplastics were identified using (micro)Raman-spectrometry, FT-IR and Py-GC-MS and cryo-milled to obtain size-fractionated samples up to 300 µm. Physiochemical MP properties were characterized using phase contrast microscopy, gel-permeation chromatography, nuclear magnetic resonance, and differential scanning colorimetry. Macrophages (differentiated THP-1 cells) were exposed to particles (<300 µm) for 48 hours before assessment of cell viability and cytokine release. Using both the physiochemical particle properties and biological data, we performed multi-dimensional data analysis to explore relationships between particle properties and immunotoxicological effects. Results: We investigated land-derived polyethylene, polypropylene, polystyrene, and polyethylene terephthalate, water-derived polypropylene macroplastics, and virgin polyethylene fibers and nylon MPs. The different plastic polymeric compositions and MP size classes induced distinct cytokine responses. Macrophages had the largest response to polyethylene terephthalate-particle exposure, including a dose-related increase in IL-1β, IL-8, and TNF-α secretion. Smaller MPs induced cytokine production at lower concentrations. Additionally, a relationship between both physical and chemical particle properties and the inflammatory response of macrophages was found. Discussion: This research shows that MP exposure could lead to an inflammatory response in vitro, depending on MP material and size. Whether this implies a risk to human health needs to be further explored.